2020
DOI: 10.1007/s13762-020-02980-x
|View full text |Cite
|
Sign up to set email alerts
|

Leachate and contact test with Lepidium sativum L. to assess the phytotoxicity of waste

Abstract: The study evaluated the use of Lepidium sativum L. to assess the phytotoxicity of three types of waste such as hazardous waste (slags from zinc to copper smelters) and nonhazardous waste (mineral–organic composite). Previous studies evaluated heavy metal leaching and the environmental impact of the tested waste. The purpose of phytotoxicity studies was to increase knowledge about this waste. Two types of tests were used to assess the phytotoxicity of wastes: germination index and accumulation test. Both tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Low contents of heavy metals (< 1 mg/l) in leachates from active landfills may indicate that the landfilled waste is mainly municipal waste, not containing these components (Naveen et al, 2017). Also in other studies, the authors reported low concentrations of heavy metals in leachates, emphasizing that their presence is not a major concern at present (Öman and Junestedt, 2008;Bożym et al, 2020). The clearly higher concentrations of chromium in the leachate (except for the landfill in Jawor) could have been caused (as in the case of chromium) by high precipitation in September 2019.…”
Section: Cl-mentioning
confidence: 83%
“…Low contents of heavy metals (< 1 mg/l) in leachates from active landfills may indicate that the landfilled waste is mainly municipal waste, not containing these components (Naveen et al, 2017). Also in other studies, the authors reported low concentrations of heavy metals in leachates, emphasizing that their presence is not a major concern at present (Öman and Junestedt, 2008;Bożym et al, 2020). The clearly higher concentrations of chromium in the leachate (except for the landfill in Jawor) could have been caused (as in the case of chromium) by high precipitation in September 2019.…”
Section: Cl-mentioning
confidence: 83%
“…high phytotoxicity: GI < 50%, moderate phytotoxicity: GI 50-80%, no phytotoxicity: GI > 80%, stimulating effect for plants: GI > 100% (Zucconi et al, 1984;Bożym et al, 2020).…”
Section: Acute Toxicity Test On White Mustard Sinapis Alba Lmentioning
confidence: 99%
“…Figure 2 shows the GI values for the leachate from the four landfills, before and after the biological treatment, dosed at different concentrations. The graphs also show the classification of phytotoxicity based on the GI values, where: GI < 50% -medium high phytotoxicity, GI within 50-80% medium moderate phytotoxicity, GI > 80% no phytotoxicity, a GI > 100% -a plant stimulating effect (Zucconi et al, 1984;Bożym et al, 2020).…”
Section: Leachate Toxicitymentioning
confidence: 99%
“…For this reason, the contact of seeds with the substrate reflects the real conditions. However, for GI tests directly on a substrate, root germination and root elongation may be more difficult to evaluate because the roots may penetrate the substrate, and consequently, a visual assessment may be more complicated (Bożym et al 2021 ). Selecting an appropriate species for the type of toxin and waste may be problematic because each of the species may be characterised by a different tolerance to contamination (Manas and De las Heras 2018 ).…”
Section: Introductionmentioning
confidence: 99%